REFRAMING FAITH IN BALKAN DOCUMENTARY FILM - Radovic??, Milja, 1971- Link ([S.l.])
1 online resource
Keywords: Reframing Faith in Balkan Documentary Film presents the first systematic study of the cinematic representations of religion in the early documentary film on the Balkan Peninsula from 1896 to 1939. By looking at faith through the concept of frame, this book sheds new light on the historical realities of the period as seen by the filmmakers and facilitates rediscovering the world of lost religious communities on the territory of Yugoslavia. Placing film language at the heart of scientific research and introducing the frame as a method of analysis, this book proposes novel ways of reading history as written on the reel.This intricate and in-depth study will interest film historians, particularly those interested in Balkan and European cinema, as well as historians of the Balkans, religion, and Eastern Europe.